Literature Review Pengaruh Gaya Hidup Masyarakat Perkotaan Terhadap Kejadian Hipertensi - mahdalena, mahdalena; Kutbi, Muhammad Amin; Ningsih, Endang Sri Purwati (Politeknik Kementerian Kesehatan Banjarmasin, 2023)
Increased blood pressure is influenced by several risk factors including age, gender, family history, genetics (risk factors that cannot be changed/controlled) and lifestyle such as smoking habits, salt consumption, consumption of saturated fat, use of used cooking oil, drinking habits alcoholic beverages, obesity, lack of physical activity, stress and use of estrogen. This study used the study literature method in various journals with the Research Gate database and Google Scholar with a feasibility test using The Joanna Briggs Institute (JBI) Critical Appraisal Cross-Sectional so that a sample of 13 was obtained. retrieved journal. Results: This literature review states that there is an influence of a stressful lifestyle and physical activity in urban communities on the incidence of hypertension. Conclusion: this literature review states that there is an influence of the urban lifestyle, namely stress and physical activity on the incidence of hypertension. And the authors hope that this research is expected to be able to change lifestyles for the better and right according to the recommendations of health workers.